Spatial patterns reveal strong abiotic and biotic drivers of zooplankton community composition in Lake Mývatn, Iceland. Issue 6 (30th June 2015) - Bartrons, Mireia; Einarsson, Árni; Nobre, Regina L. G.; Herren, Cristina M.; Webert, Kyle C.; Brucet, Sandra; Ólafsdóttir, Sólveig R.; Ives, Anthony R.
Abstract : Spatial patterns in the abundance of species are determined by local abiotic and biotic conditions, and by the movement of individuals among localities. For species distributed among discrete habitat "islands", such as zooplankton distributed among lakes, local conditions within lakes often dominate low movement rates among lakes to determine the composition of communities. Here, we ask whether the same abiotic and biotic environmental conditions can generate spatial patterns in the distribution of zooplankton within a lake where there are high horizontal movement rates. We conducted three spatial surveys of zooplankton communities in Lake Mývatn, Iceland, a moderately sized (37 km 2 ) shallow lake with a high outflow rate. The pelagic zooplankton community showed strong spatial structure (spatial autocorrelation), with species composition varying with spatial variation in chlorophyll‐a, the abundance of Anabaena (cyanobacteria), lake depth, light extinction coefficient, and temperature. These factors are known from other studies to be strong drivers of among‐lake variation in freshwater zooplankton communities. However, in contrast with among‐lake studies, fish (stickleback) abundance had no measureable effect on the abundance or species composition of the zooplankton community, although high local stickleback abundance was associated with low zooplankton:phytoplankton biomass ratios. Finally, a parallel study of the underlying benthic crustacean community showed much finer spatial variation (spatial autocorrelation to a range ≤0.6 km vs. 9 km for pelagic zooplankton), suggesting that the stationary character of the benthos allows finer grained spatial patterns. Given the high flow rate of water in Mývatn (>200 m/d), the generation of spatial patterns suggests very strong effects of variation in abiotic and biotic environmental conditions on the population dynamics of zooplankton in the lake.